Response of high leaf-oil Arabidopsis thaliana plant lines to biotic or abiotic stress - Yurchenko, Olga (Plant Signal Behav, 2018)
Recent studies have shown that it is possible to engineer substantial increases in triacylglycerol (TAG) content in plant vegetative biomass, which offers a novel approach for increasing the energy density of food, feed, and bioenergy crops or for creating a sink for the accumulation of unusual, high-value fatty acids. However, whether or not these changes in lipid metabolism affect plant responses to biotic and/or abiotic stresses is an open question. Here we show that transgenic Arabidopsis thaliana plant lines engineered for elevated leaf oil content, as well as lines engineered for accumulation of unusual conjugated fatty acids in leaf oil, had similar short-term responses to heat stress (e.g., 3 days at 37°C) as wild-type plants, including a reduction in polyunsaturated fatty acid (PUFA)-containing polar lipids and an increase in PUFA-containing neutral lipids. At extended time periods (e.g., 14 days at 37°C), however, plant lines containing accumulated conjugated fatty acids displayed earlier senescence and plant death. Further, no-choice feeding studies demonstrated that plants with the highest leaf oil content generated cabbage looper (Trichoplusia ni) insects with significantly heavier body weights. Taken together, these results suggest that biotic and abiotic responses will be important considerations when developing and deploying high-oil-biomass crops in the field.